Promt Scaffolding in Learning Life Skills for Self-Development of Intellectual Disabilities Students in Inclusive Primary School - Widajati, Wiwik; Mahmudah, Siti (Jurnal Pendidikan Indonesia, 2022)
Scaffolding promt plays an important role in improving the life skills of students with intellectual disabilities so that they are independent in their daily activities. This study aims to investigate the relationship and importance of scaffolding promt in the context of learning the life skills of students with intellectual disabilities at SD inclusive. This research was conducted on Inclusive primary school students. The data collection tool used is a self-development life skill performance test consisting of 22 items. Data analysis using Pearson product moment. Based on the analysis of research data, there is a significant relationship between scaffolding promt by increasing the life skills of intellectual disability students with intellectual disabilities in SD inclusive. The results of the study also showed the importance of scaffolding promt because it made a significant contribution to increasing the independence of students with intellectual disabilities in carrying out life skills in the context of real life. The limitations of this research only cover students with mental retardation in the scope of inclusive primary schools, so that more extensive further research is needed.